In-depth Chemistry and Pharmacological Potential of Propolis: A Critical Review of Recent Developments - Dwivedi, Jyotsana; Sachan, Pranjal; Wal, Pranay; Rai, A. K. (Current Traditional Medicine, 2024)
Background: One of the most popular beekeeping products is propolis. The word
Keywords: Propolis